O hiperprecariado em movimento: a territorialização contraditória da luta por moradia em João Pessoa-PB - Lima, Thiago Almeida de (2017)
This thesis is about the political struggle performed by the people who daily experience the most perverse effects of the process of capital's productive restructuring in semi-periphery countries, especially in the urban peripheries of Brazil - the hyperprecariat. Face to the multiple forms of resistance expression and insurgency starred by subalternized population groups in Brazilian cities, those binded to the issue of housing are certainly the most prominent, not only because it is a basic right that is not universalized, but also because of the deeply selective characteristic that characterizes the production of urban space in the country. In a national scenario marked by the generalized sensation of crisis, by the increment of proto-fascist manifestations and by a worrisome advance of capital over the incipient social rights conquered, there has been occurring the deepening of the critical situation that has affected the emancipatory movements in the last three decades. In this context, it is important the necessity to reflect about contradictions that mark the political-doing of the people who belong to the hyperprecariat social spheres, in the perspective of revealing their most intimate conditions. In order to accomplish this task, we will rest our analysis on the experiences of struggle for housing articulated by 'Free land - Popular Movement of the Countryside and the City' in João Pessoa-PB. Looking at the daily life of the territories built by and from the political struggle performed by the mentioned social movement, we aim to highlight their spatial practices, emphasizing the contradictions inscribed in them, pointing out, besides the specificities that frame the political-doing of the urban hyperprecariat, their possibilities and limits. The reflections developed during this research allowed to formulate the thesis that the hyperprecariat, when put in moviment in the search for the realization of the right to housing, promotes a contradictory territorialisation of the struggle, full of specificities and characterized, among other aspects, by the coexistence of socio-spatial practices insurgents and repetitives of the established order.